The Effect of Delivery Types on Preschoolers’ Weight: A Case-control Study - Mousavi , Seyad Asghar; Sheikh Fathollahi , Mahmood; Rezaiyan, Mohsen; Vaziriynejad, Reza; Ahmadinia, Hassan; Manshouri , Azita; Daneshi, Salman; Sheikh Beig Goharrizi, Mohammad Ali; Vazirinejad, Reza (Archives of Advances in Biosciences, 2021)
Introduction: This study was designed to determine the effect of delivery type on obesity of children. Materials and Methods: This case-control study investigated preschoolers in Rafsanjan city in 2018. The study population was divided into two groups. The first group consisted of children who were overweight and obese as the case group, the second group included children with normal BMI as the control group. For each obese and overweight child, a normal-weight child was considered his or her control, matching the preschool center, sex and age. Logistic regression models were used to examine the relationship and calculate the odds ratio. Results: Data for 171 paired children were collected. Results showed that 126 (73.7%) of the case group and 115 (67.3%) of the control group were born through CS. The odds of obesity and overweight in children born through CS was 1.363 times higher than those born through normal delivery but this difference was not statistically significant (P = .193). These results did not change after controlling the effect of confounding factors. Also, the risk of obesity and overweight in children born from mothers who had cesarean selective delivery was 1.523 times higher than those born through normal delivery, but this difference was not statistically significant (P = .275). Conclusion: The findings of our study did not show any evidence of a relationship between maternal type of delivery and childhood weight. In this study, obesity and childhood overweight depended on maternal characteristics. Key words: Obesity, Overweight, Preschoolers, Case-Control Study